Environment-friendly shaving board and preparation method thereof
By combining environmentally friendly flame-retardant and mildew-proof adhesives that closely combine phytic acid, graphene and soy protein with bamboo and wood waste, environmentally friendly particle board is prepared, which solves the problems of particle board's hygroscopicity, poor anti-mold effect and flammability. , achieving higher flame retardant performance, mildew resistance and environmental protection.
Patent Information
- Application Number
- CN202411536076.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Existing particleboards have high hygroscopicity, poor mildew resistance, easy to release formaldehyde gas, poor environmental protection, easy to burn at high temperatures, and poor flame retardancy.
By preparing quaternary ammonium salt epoxy antibacterial agents, phytic acid, graphene and soy protein are closely combined to form an environmentally friendly flame-retardant and anti-mold adhesive, and bamboo and wood waste is prepared by shaving, mixing glue and hot pressing. Environmentally friendly particle board.
It significantly improves the flame retardant performance, mildew resistance and environmental protection of particleboard, reduces formaldehyde emission, and enhances the water resistance and mechanical properties of the board.
Smart Images

Figure BDA0005111576510000051 
Figure BDA0005111576510000052 
Figure BDA0005111576510000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of furniture boards, in particular to an environmentally friendly particle board and a preparation method thereof. Background Art
[0002] Particleboard is a type of man-made board. It is a board made by pressing wood chips or other wood fiber material chips with adhesives under a certain temperature and pressure. It can be used to make furniture, counters, floors, walls and office supplies. In the preparation process of particleboard, adhesives play a key role in bonding the wood particles together to form a stable structure. Therefore, the performance and environmental friendliness of adhesives directly affect the overall quality and environmental protection level of particleboard. In the preparation of traditional particleboard, commonly used adhesives such as urea-formaldehyde resin glue may release harmful substances such as free formaldehyde, which will harm the environment and human health and have poor environmental performance. If such environmental issues are not properly handled, it will inevitably affect the overall development of particleboard.
[0003] The main raw materials of particleboard are wood chips and adhesives. Natural adhesives such as soy protein adhesives can significantly reduce formaldehyde emissions, and even reach the standard of no formaldehyde emissions. However, they have low strength and poor water resistance. At the same time, existing particleboards have high hygroscopicity, poor anti-corrosion and anti-mildew effects, and are prone to breeding bacteria in humid environments, resulting in a short service life. In addition, the raw materials of particleboard are mainly composed of cellulose, hemicellulose and lignin, which are flammable and easy to burn at high temperatures, releasing flammable gases and heat, thus causing fires. Patent No. CN106 863528B discloses a method for preparing an antibacterial and mildew-proof environment-friendly particleboard, comprising the steps of fully stirring a modified defatted soybean powder paste, a leveling agent, an organic bentonite and an auxiliary agent to obtain an agent A; adding propolis powder, an antioxidant and an emulsifier to mix to obtain an agent B; and mixing the agent A and the agent B at a mass ratio of 4-5:1 to obtain an adhesive, which utilizes the natural broad-spectrum antibacterial and bactericidal properties of propolis to achieve the mildew-proof effect. However, the method is complicated to use and requires the preparation of a two-component adhesive, and has limited mildew-proof and antibacterial effects. Furthermore, the flame retardant properties of the particleboard are not improved, and the method is not suitable for industrial production.
[0004] In the prior art, inorganic flame retardants or mildew-proof agents are generally added to achieve flame retardancy and mildew-proofing, but the prepared particleboard has a certain odor, which affects the indoor environment quality of people's lives and is not environmentally friendly. In addition, too much inorganic filler will reduce the mechanical properties of the particleboard. The present invention aims to prepare a quaternary ammonium salt epoxy antibacterial agent, and closely combine phytic acid, graphene, and soy protein through multiple bonding reactions to achieve the enhancement and toughening of the particleboard, green environmental protection, mildew-proof and flame-retardant, and broaden the application range of the particleboard. Summary of the invention
[0005] The purpose of the present invention is to solve the problems in the prior art that particleboard has high hygroscopicity, poor mildew resistance, easy release of formaldehyde gas, poor environmental protection, easy combustion at high temperature and poor flame retardancy, and to provide an environmentally friendly particleboard and a preparation method thereof.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for preparing an environmentally friendly particleboard comprises the following steps:
[0008] Step (1), preparing wood shavings: peeling, screening and removing impurities from bamboo and wood waste, adding the waste to a pulverizer, and processing the waste into wood shavings with a length of 100-120 mm, a width of 20-50 mm and a thickness of 0.3-0.5 mm to obtain wood shavings raw materials.
[0009] Step (2), preparing rubber-mixed wood shavings: drying the wood shavings raw material, placing them in a drum rubber mixer, adding environmentally friendly flame retardant and mildew-proof adhesive and paraffin wax, stirring at 500-800 r / min for 1-3 hours, and drying to a moisture content of 3-5wt% to obtain rubber-mixed wood shavings.
[0010] Step (3), preparing an environmentally friendly particleboard: manually laying the mixed glue wood chips into a single-layer slab, installing it in a steel film frame to form a three-layer structure of an upper and lower surface layer and a core layer, placing it in a hot press for hot pressing, demolding and curing, and obtaining an environmentally friendly particleboard.
[0011] Preferably, in step (2), the mass ratio of wood shavings raw material, environmentally friendly flame retardant and mildew-proof adhesive, and paraffin is 100:3-15:2-4.
[0012] Preferably, in step (3), the hot pressing pressure is 3-6 MPa, the hot pressing time is 8-15 min, and the hot pressing temperature is 130-150°C.
[0013] Preferably, the method for preparing the environmentally friendly flame retardant and mildew-proof adhesive in step (2) comprises the following steps:
[0014] Step S1, under a nitrogen atmosphere, add pentaerythritol glycidyl ether and ethanol into a reaction flask, stir evenly, add hexadecyl dimethyl tertiary amine and hydrochloric acid, stir to react, and after the reaction is completed, perform vacuum distillation, and recrystallize with a mixed solvent of acetone and ethyl acetate to obtain a long-chain quaternary ammonium salt intermediate.
[0015] Step S2, under a nitrogen atmosphere, add a long-chain quaternary ammonium salt intermediate and acetonitrile to a reaction flask, stir evenly, add epichlorohydrin and sodium hydroxide, stir to react, and after the reaction is completed, perform reduced pressure distillation to obtain a polyepoxy quaternary ammonium salt cross-linking agent.
[0016] Step S3, the soy protein, polyhydroxyphytic acid, and graphene oxide dispersion are mixed evenly, ultrasonically treated for 15-25 minutes, and then a polyepoxy quaternary ammonium salt crosslinker is added, placed in a high-speed shear dispersion homogenizer, and vigorously homogenized at room temperature for 20-40 minutes to obtain an environmentally friendly flame retardant and mildew-proof adhesive.
[0017] Preferably, in step S1, the mass ratio of pentaerythritol glycidyl ether, hexadecyl dimethyl tertiary amine, and hydrochloric acid is 100:305-330:15-25.
[0018] Preferably, in step S1, the reaction temperature is 65-80° C. and the reaction time is 24-48 h.
[0019] Preferably, in step S2, the mass ratio of the long-chain quaternary ammonium salt intermediate, epichlorohydrin, and sodium hydroxide is 100:28-40:10-15.
[0020] Preferably, in step S2, the reaction temperature is 45-60° C. and the reaction time is 5-12 h.
[0021] Preferably, in step S3, the mass ratio of soy protein, polyhydroxyphytic acid, graphene oxide dispersion, and polyepoxy quaternary ammonium salt crosslinking agent is 100:4-8:20-35:2-10.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The invention uses pentaerythritol glycidyl ether, hexadecyl dimethyl tertiary amine and epichlorohydrin as raw materials, obtains a polyepoxy quaternary ammonium salt cross-linking agent through a chemical reaction, and then closely connects soybean protein, polyhydroxyphytic acid and graphene oxide through the cross-linking agent to obtain an environmentally friendly flame-retardant and mildew-proof adhesive, and then obtains an environmentally friendly particleboard after shaving, mixing with glue and hot-pressing bamboo and wood waste.
[0024] Polyhydroxyphosphoric acid is rich in phosphorus. As the combustion proceeds, molecular interactions occur between the adhesive components, and rapid carbonization is formed through the thermal condensation of the phosphorus functional groups of the polyhydroxyphytic acid molecules, which reduces the flammability of the material. At the same time, the layered structure of graphene oxide has a stronger physical barrier effect than traditional inorganic compounds in protecting carbonized residues, providing a heat shielding effect for the carbonized layer, effectively preventing the volatilization of smoke particles during combustion, and increasing the diffusion path of oxygen and heat sources, thereby improving the flame retardant properties of particleboard. In addition, phytic acid and soy protein are low-cost and widely available biomass materials, which are non-toxic and harmless, do not release formaldehyde, and are green and pollution-free. Its structure contains antibacterial quaternary ammonium salt groups, which have a good preventive and control effect on mold and discoloration bacteria. It is adsorbed to the cell surface of mold and discoloration bacteria through electrostatic adsorption, and then its hydrophobic long-chain alkyl group is inserted into the lipid layer of the cell membrane, changing the permeability of the cell membrane, disrupting the composition of the cell membrane, causing disorder in the cell membrane structure, affecting the normal physiological function of the cell, and ultimately leading to cell death.
[0025] The polyhydroxyphytic acid in the environmentally friendly flame retardant and mildew-proof adhesive contains a ring structure of multi-dentate ligands. The abundant hydroxyl groups in its structure have strong hydrogen bonding forces with graphene oxide, which enables the phytic acid to be inserted into the interlayer spacing of the graphene sheets and cross-linked with multiple graphene sheets to form a dense cross-linked network structure; the chain end of the polyepoxy quaternary ammonium salt cross-linker molecule has four epoxy groups, which can undergo a ring-opening reaction with the hydroxyl groups in the phytic acid and the amino groups in the soy protein to form a covalent bonding interface; the polyepoxy quaternary ammonium salt cross-linker is equivalent to a physical cross-linking point in the particleboard, and is "anchored" together with the bamboo and wood particles by the adhesive, which will limit the further expansion of microcracks into large cracks, making the slab denser and having a strengthening and toughening effect. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described in detail below in conjunction with specific examples; the following examples will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in this application are all commercially available products or can be prepared by known methods.
[0027] Soy protein (46% protein) was purchased from Shandong Xiangchi Grain and Oil Co., Ltd., China.
[0028] Pentaerythritol glycidyl ether, CAS number is 3126-63-4.
[0029] Hexadecyl dimethyl tertiary amine, CAS number is 112-69-6.
[0030] Preparation of polyhydroxyphytic acid: Add 4.36g of pentaerythritol and 27.23g of phytic acid into a 250mL three-necked flask and mix well, then heat to 120°C and react for 3h to obtain a crude product, and finally vacuum filter and freeze-dry to obtain polyhydroxyphytic acid. The preparation reaction formula is as follows:
[0031]
[0032] Preparation of graphene oxide dispersion: 2.4 g of graphite powder and 8 g of NaNO3 were mixed in 140 mL of concentrated H2SO4, and the resulting mixture was stirred in an ice bath for 2 h, and then 12 g of KMnO4 was dropped into the above prepared solution at a rate of 1 g / min. After the reaction was carried out for 5 h, 500 mL of deionized water was added to the above reaction vessel, and then the resulting mixture was stirred at 35 ° C for 60 min. After stirring, a large amount of water and 10 mL of H2O2 were used to terminate the reaction; the prepared product was placed for 48 hours, and then centrifuged and purified using a 30% mass fraction HCl solution, and ultrasonically treated for 30 minutes to obtain a graphene oxide dispersion.
[0033] Example 1
[0034] (1) Under nitrogen atmosphere, 35 g of pentaerythritol glycidyl ether and 280 mL of ethanol were added to a reaction flask, and after stirring, 112 g of hexadecyl dimethyl tertiary amine and 75 g of 30% hydrochloric acid were added, and the mixture was reacted at 75° C. for 32 h, and then distilled under reduced pressure, and recrystallized from a mixed solvent of acetone and ethyl acetate to obtain a long-chain quaternary ammonium salt intermediate. The preparation reaction formula is as follows:
[0035]
[0036] (2) Under nitrogen atmosphere, 30 g of long-chain quaternary ammonium salt intermediate and 300 mL of acetonitrile were added to a reaction flask, and after stirring, 9.6 g of epichlorohydrin and 3.6 g of sodium hydroxide were added, and the mixture was reacted at 55° C. for 10 h, and then distilled under reduced pressure to obtain a polyepoxy quaternary ammonium salt crosslinking agent. The preparation reaction formula is as follows:
[0037]
[0038] (3) 100 g of soy protein, 5 g of polyhydroxyphytic acid, and 25 g of graphene oxide dispersion with a mass concentration of 2 g / mL were mixed evenly, ultrasonically treated for 20 min, and then 2 g of polyepoxy quaternary ammonium salt crosslinker was added. The mixture was placed in a high-speed shear dispersion homogenizer and vigorously homogenized at room temperature for 30 min to obtain an environmentally friendly flame retardant and mildew-proof adhesive.
[0039] (4) peeling, screening and removing impurities from bamboo and wood waste, adding them into a pulverizer, processing them into wood chips with a length of 110 mm, a width of 30 mm and a thickness of 0.4 mm, and obtaining wood chip raw materials; drying 100 g of wood chip raw materials, placing them in a drum glue mixer, adding 3 g of an environmentally friendly flame retardant and mildew-proof adhesive and 3 g of paraffin wax, stirring and treating them at 650 r / min for 2 h, and drying them to a moisture content of 4 wt % to obtain glue-mixed wood chips; manually laying the glue-mixed wood chips into a single-layer slab, installing them in a steel film frame and laying them into a three-layer structure of an upper and lower surface layer and a core layer, placing them in a hot press for hot pressing molding, the hot pressing pressure is 5 MPa, the hot pressing time is 12 min, and the hot pressing temperature is 140° C., followed by demolding and curing for 7 days to obtain an environmentally friendly particleboard.
[0040] Example 2
[0041] (1) Under a nitrogen atmosphere, 52 g of pentaerythritol glycidyl ether and 260 mL of ethanol were added to a reaction flask, and after stirring, 158.6 g of hexadecyl dimethyl tertiary amine and 7.8 g of 30% hydrochloric acid were added, and the mixture was reacted at 80° C. for 24 h, and then distilled under reduced pressure and recrystallized with a mixed solvent of acetone and ethyl acetate to obtain a long-chain quaternary ammonium salt intermediate.
[0042] (2) Under a nitrogen atmosphere, 45 g of a long-chain quaternary ammonium salt intermediate and 360 mL of acetonitrile were added to a reaction flask. After stirring evenly, 12.6 g of epichlorohydrin and 4.5 g of sodium hydroxide were added. The mixture was reacted at 60° C. for 5 h, and then distilled under reduced pressure to obtain a polyepoxy quaternary ammonium salt crosslinking agent.
[0043] (3) 100 g of soy protein, 4 g of polyhydroxyphytic acid, and 20 g of graphene oxide dispersion with a mass concentration of 2 g / mL were mixed evenly, ultrasonically treated for 25 min, and then 4 g of polyepoxy quaternary ammonium salt crosslinker was added. The mixture was placed in a high-speed shear dispersion homogenizer and vigorously homogenized at room temperature for 20 min to obtain an environmentally friendly flame retardant and mildew-proof adhesive.
[0044] (4) peeling, screening and removing impurities from bamboo and wood waste, adding them into a pulverizer, processing them into wood chips with a length of 100 mm, a width of 20 mm and a thickness of 0.3 mm, and obtaining wood chip raw materials; drying 100 g of wood chip raw materials, placing them in a drum glue mixer, adding 6 g of an environmentally friendly flame-retardant and mildew-proof adhesive and 2 g of paraffin wax, stirring them at 800 r / min for 1 h, and drying them to a moisture content of 5 wt % to obtain glue-mixed wood chips; manually laying the glue-mixed wood chips into a single-layer slab, installing them in a steel film frame and laying them into a three-layer structure of an upper and lower surface layer and a core layer, placing them in a hot press for hot pressing molding, the hot pressing pressure is 6 MPa, the hot pressing time is 8 min, and the hot pressing temperature is 150° C., followed by demolding and curing for 7 days to obtain an environmentally friendly particleboard.
[0045] Example 3
[0046] (1) Under a nitrogen atmosphere, 12 g of pentaerythritol glycidyl ether and 120 mL of ethanol were added to a reaction flask, and after stirring, 39.6 g of hexadecyl dimethyl tertiary amine and 3 g of 30% hydrochloric acid were added, and the mixture was reacted at 65° C. for 48 h, and then distilled under reduced pressure and recrystallized with a mixed solvent of acetone and ethyl acetate to obtain a long-chain quaternary ammonium salt intermediate.
[0047] (2) Under a nitrogen atmosphere, 10 g of a long-chain quaternary ammonium salt intermediate and 80 mL of acetonitrile were added to a reaction flask. After stirring evenly, 4 g of epichlorohydrin and 1.5 g of sodium hydroxide were added. The mixture was reacted at 45° C. for 12 h, and then distilled under reduced pressure to obtain a polyepoxy quaternary ammonium salt crosslinking agent.
[0048] (3) 100 g of soy protein, 8 g of polyhydroxyphytic acid, and 35 g of graphene oxide dispersion with a mass concentration of 2 g / mL were mixed evenly, ultrasonically treated for 25 min, and then 6 g of polyepoxy quaternary ammonium salt crosslinker was added. The mixture was placed in a high-speed shear dispersion homogenizer and vigorously homogenized at room temperature for 40 min to obtain an environmentally friendly flame retardant and mildew-proof adhesive.
[0049] (4) peeling, screening and removing impurities from bamboo and wood waste, adding them into a pulverizer, processing them into wood chips with a length of 120 mm, a width of 50 mm and a thickness of 0.5 mm, and obtaining wood chip raw materials; drying 100 g of wood chip raw materials, placing them in a drum glue mixer, adding 9 g of an environmentally friendly flame-retardant and mildew-proof adhesive and 4 g of paraffin wax, stirring and treating them at 500 r / min for 3 h, and drying them to a moisture content of 3 wt % to obtain glue-mixed wood chips; manually laying the glue-mixed wood chips into a single-layer slab, installing them in a steel film frame and laying them into a three-layer structure of an upper and lower surface layer and a core layer, placing them in a hot press for hot pressing molding, the hot pressing pressure is 3 MPa, the hot pressing time is 15 min, and the hot pressing temperature is 130° C., followed by demolding and curing for 7 days to obtain an environmentally friendly particleboard.
[0050] Example 4
[0051] (1) Under a nitrogen atmosphere, 25 g of pentaerythritol glycidyl ether and 150 mL of ethanol were added to a reaction flask, and after stirring, 793 g of hexadecyl dimethyl tertiary amine and 5.5 g of 30% hydrochloric acid were added, and the mixture was reacted at 70° C. for 30 h, and the mixture was distilled under reduced pressure and recrystallized with a mixed solvent of acetone and ethyl acetate to obtain a long-chain quaternary ammonium salt intermediate.
[0052] (2) Under a nitrogen atmosphere, 18 g of a long-chain quaternary ammonium salt intermediate and 170 mL of acetonitrile were added to a reaction flask. After stirring evenly, 6.3 g of epichlorohydrin and 2.45 g of sodium hydroxide were added. The mixture was reacted at 50° C. for 9 h, and then distilled under reduced pressure to obtain a polyepoxy quaternary ammonium salt crosslinking agent.
[0053] (3) 100 g of soy protein, 7 g of polyhydroxyphytic acid, and 30 g of graphene oxide dispersion with a mass concentration of 2 g / mL were mixed evenly, ultrasonically treated for 18 min, and then 8 g of polyepoxy quaternary ammonium salt crosslinker was added. The mixture was placed in a high-speed shear dispersion homogenizer and vigorously homogenized at room temperature for 35 min to obtain an environmentally friendly flame retardant and mildew-proof adhesive.
[0054] (4) peeling, screening and removing impurities from bamboo and wood waste, adding them into a pulverizer, processing them into wood chips with a length of 105 mm, a width of 25 mm and a thickness of 0.35 mm, and obtaining wood chip raw materials; drying 100 g of wood chip raw materials, placing them in a drum glue mixer, adding 12 g of an environmentally friendly flame retardant and mildew-proof adhesive and 4 g of paraffin wax, stirring and treating them at 750 r / min for 2 h, and drying them to a moisture content of 4 wt % to obtain glue-mixed wood chips; manually laying the glue-mixed wood chips into a single-layer slab, installing them in a steel film frame and laying them into a three-layer structure of an upper and lower surface layer and a core layer, placing them in a hot press for hot pressing molding, the hot pressing pressure is 5 MPa, the hot pressing time is 12 min, and the hot pressing temperature is 145° C., followed by demolding and curing for 7 days to obtain an environmentally friendly particleboard.
[0055] Example 5
[0056] (1) Under a nitrogen atmosphere, 8 g of pentaerythritol glycidyl ether and 75 mL of ethanol were added to a reaction flask, stirred evenly, and then 26 g of hexadecyl dimethyl tertiary amine and 2 g of 30% hydrochloric acid were added. The mixture was reacted at 80° C. for 48 h, and distilled under reduced pressure. The mixture was recrystallized with a mixed solvent of acetone and ethyl acetate to obtain a long-chain quaternary ammonium salt intermediate.
[0057] (2) Under a nitrogen atmosphere, 5 g of the long-chain quaternary ammonium salt intermediate and 50 mL of acetonitrile were added to a reaction flask. After stirring evenly, 1.8 g of epichlorohydrin and 0.7 g of sodium hydroxide were added. The mixture was reacted at 55° C. for 12 h, and then distilled under reduced pressure to obtain a polyepoxy quaternary ammonium salt crosslinking agent.
[0058] (3) 100 g of soy protein, 6 g of polyhydroxyphytic acid, and 30 g of graphene oxide dispersion with a mass concentration of 2 g / mL were mixed evenly, ultrasonically treated for 25 min, and then 10 g of polyepoxy quaternary ammonium salt crosslinker was added. The mixture was placed in a high-speed shear dispersion homogenizer and vigorously homogenized at room temperature for 40 min to obtain an environmentally friendly flame retardant and mildew-proof adhesive.
[0059] (4) peeling, screening and removing impurities from bamboo and wood waste, adding them to a pulverizer, processing them into wood chips with a length of 110 mm, a width of 45 mm and a thickness of 0.45 mm, and obtaining wood chip raw materials; drying 100 g of wood chip raw materials, placing them in a drum glue mixer, adding 15 g of an environmentally friendly flame-retardant and mildew-proof adhesive and 3 g of paraffin wax, stirring and treating them at 750 r / min for 3 h, and drying them to a moisture content of 5 wt % to obtain glue-mixed wood chips; manually laying the glue-mixed wood chips into a single-layer slab, installing them in a steel film frame and laying them into a three-layer structure of an upper and lower surface layer and a core layer, placing them in a hot press for hot pressing molding, the hot pressing pressure is 5 MPa, the hot pressing time is 15 min, and the hot pressing temperature is 150° C., followed by demolding and curing for 7 days to obtain an environmentally friendly particleboard.
[0060] Comparative Example 1
[0061] (1) 100 g of soy protein, 5 g of polyhydroxyphytic acid, and 25 g of graphene oxide dispersion with a mass concentration of 2 g / mL were mixed evenly, ultrasonically treated for 20 min, and then 2 g of pentaerythritol glycidyl ether was added. The mixture was placed in a high-speed shear dispersion homogenizer and vigorously homogenized at room temperature for 30 min to obtain an environmentally friendly adhesive.
[0062] (2) peeling, screening and removing impurities from bamboo and wood waste, adding them into a pulverizer, processing them into wood chips with a length of 110 mm, a width of 30 mm and a thickness of 0.4 mm, and obtaining wood chip raw materials; drying 100 g of wood chip raw materials, placing them into a drum glue mixer, adding 3 g of environmentally friendly adhesive and 3 g of paraffin wax, stirring them at 650 r / min for 2 h, and drying them to a moisture content of 4 wt % to obtain glue-mixed wood chips; manually laying the glue-mixed wood chips into a single-layer slab, installing them in a steel film frame and laying them into a three-layer structure of an upper and lower surface layer and a core layer, placing them in a hot press for hot pressing molding, the hot pressing pressure is 5 MPa, the hot pressing time is 12 min, and the hot pressing temperature is 140° C., followed by demolding and curing for 7 days to obtain a particleboard.
[0063] Comparative Example 2
[0064] (1) 100 g of soy protein and 25 g of a graphene oxide dispersion with a mass concentration of 2 g / mL were mixed evenly, and ultrasonically treated for 20 min. Then, 2 g of a polyepoxy quaternary ammonium salt crosslinker (prepared in Example 1) was added, and the mixture was placed in a high-speed shear dispersion homogenizer and vigorously homogenized at room temperature for 30 min to obtain an environmentally friendly adhesive.
[0065] (2) peeling, screening and removing impurities from bamboo and wood waste, adding them into a pulverizer, processing them into wood chips with a length of 110 mm, a width of 30 mm and a thickness of 0.4 mm, and obtaining wood chip raw materials; drying 100 g of wood chip raw materials, placing them into a drum glue mixer, adding 3 g of environmentally friendly adhesive and 3 g of paraffin wax, stirring them at 650 r / min for 2 h, and drying them to a moisture content of 4 wt % to obtain glue-mixed wood chips; manually laying the glue-mixed wood chips into a single-layer slab, installing them in a steel film frame and laying them into a three-layer structure of an upper and lower surface layer and a core layer, placing them in a hot press for hot pressing molding, the hot pressing pressure is 5 MPa, the hot pressing time is 12 min, and the hot pressing temperature is 140° C., followed by demolding and curing for 7 days to obtain a particleboard.
[0066] Comparative Example 3
[0067] The bamboo and wood waste is peeled, sieved and impurities removed, and added into a pulverizer to be processed into wood chips with a length of 110 mm, a width of 30 mm and a thickness of 0.4 mm to obtain wood chip raw materials; 100 g of the wood chip raw materials are dried, placed in a drum glue mixer, 3 g of phenolic resin adhesive (commercially available) and 3 g of paraffin wax are added, stirred at 650 r / min for 2 hours, and dried to a moisture content of 4 wt % to obtain glue-mixed wood chips; the glue-mixed wood chips are manually laid into a single-layer slab, installed in a steel film frame to form a three-layer structure of an upper and lower surface layer and a core layer, and placed in a hot press for hot pressing molding, the hot pressing pressure is 5 MPa, the hot pressing time is 12 min, and the hot pressing temperature is 140°C, followed by demolding and curing for 7 days to obtain a particleboard.
[0068] Anti-mildew performance test: Referring to GB / T 18261-2013 standard, the prepared particle board was tested for anti-mildew performance, and each group was repeated three times to take the average value.
[0069] The experimental molds (Aspergillus niger, Trichoderma viride) and color-changing fungi (Diplodia theobroma cacao, Fusarium moniliforme) were purchased from Ningbo Mingzhou Biotechnology Co., Ltd.
[0070] Infection value: 0, no hyphae or mildew spots on the surface of the sample.
[0071] Infection value: 1, the infected area of the sample surface is less than 1 / 4.
[0072] Infection value: 2, the infected area of the sample surface is 1 / 4-1 / 2.
[0073] Infection value: 3, the infected area of the sample surface is 1 / 2-3 / 4.
[0074] Infection value: 4, the infected area of the sample surface is greater than 3 / 4.
[0075] Table 1 Anti-mildew performance test
[0076] Aspergillus niger Trichoderma viride Diplosporus cocoi Fusarium moniliforme Example 1 1 1 1 1 Example 2 1 1 1 0 Example 3 0 1 1 0 Example 4 0 0 0 0 Example 5 0 0 0 0 Comparative Example 1 3 3 4 4 Comparative Example 2 1 0 1 1 Comparative Example 3 4 4 4 4
[0077] During the sample culture process, the mold growth on the sample is observed regularly, the mold area of the sample is measured and the mold grade is evaluated. The smaller the infection value, the better the mold-proof effect. It can be seen from the test results in the above table that with the increase of the content of the environmentally friendly flame-retardant and mildew-proof adhesive, the mildew-proof performance of the particleboard is gradually enhanced, and it has a good control effect on mold and discoloration bacteria. This is because the environmentally friendly flame-retardant and mildew-proof adhesive contains antibacterial quaternary ammonium salt groups, which are first adsorbed to the cell surface of mold and discoloration bacteria through electrostatic adsorption, and then its hydrophobic long-chain alkyl group is inserted into the lipid layer of the cell membrane, changing the permeability of the cell membrane, disrupting the composition of the cell membrane, causing the cell membrane structure to be chaotic, affecting the normal physiological function of the cell, and finally causing cell death. Comparative Examples 1 and 3 do not contain quaternary ammonium salt antibacterial groups, do not have mold-proof effects, and have poor control effects on mold and discoloration bacteria.
[0078] Table 2 Flame retardant and environmental performance test
[0079]
[0080] Particleboard is a flammable material and poses a fire safety hazard when used in public places or crowded places. Improving the flame retardancy of the adhesive can reduce the fire risk of plywood to a certain extent. It can be seen from the test results in the above table that with the increase in the content of the environmentally friendly flame retardant and mildew-proof adhesive, the flame retardant performance of the particleboard is gradually enhanced, and the limiting oxygen index in Example 4 reaches 35.4%, reaching the level of flame-retardant materials. This is because the polyhydroxyphosphoric acid in the environmentally friendly flame retardant and mildew-proof adhesive is rich in phosphorus. As the combustion proceeds, molecular interactions occur between the adhesive components, and rapid carbonization is formed through the thermal condensation of the phosphorus functional groups of the polyhydroxyphytic acid molecules, thereby reducing the flammability of the material. At the same time, the layered structure of graphene oxide has a stronger physical barrier effect in protecting carbonized residues than traditional inorganic compounds, providing a heat shielding effect for the carbonized layer, effectively preventing the volatilization of smoke particles during combustion, and increasing the diffusion path of oxygen and heat sources, thereby improving the flame retardant performance of the particleboard. In addition, phytic acid and soy protein are low-cost and widely available biomass materials, which are non-toxic, harmless, and do not release formaldehyde, and are green, environmentally friendly, and pollution-free. Comparative Example 3 uses a commercially available phenolic resin adhesive, which releases a high amount of formaldehyde and is harmful to human health.
[0081] Mechanical properties test: Referring to the standard GB / T 17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneer wood-based panels", a microcomputer-controlled electronic mechanical testing machine was used to test the physical and mechanical properties of the prepared particleboard, such as elastic modulus, internal bonding strength, and water absorption thickness expansion rate.
[0082] Table 3 Mechanical properties test
[0083]
[0084] From the test results in the above table, it can be seen that the prepared particleboard is more waterproof, has high bonding strength and good mechanical properties. This is because the polyhydroxy phytic acid in the environmentally friendly flame retardant and mildew-proof adhesive contains a ring structure of multi-dentate ligands, and there is a strong hydrogen bond force between the abundant hydroxyl groups in its structure and graphene oxide, so that the phytic acid can be inserted into the interlayer spacing of the graphene sheet and cross-linked with multiple graphene sheets to form a dense cross-linked network structure; the chain end of the polyepoxy quaternary ammonium salt cross-linker molecule has four epoxy groups, which can react with the hydroxyl groups in the phytic acid and the amino groups in the soy protein to form a covalent bonding interface; the polyepoxy quaternary ammonium salt cross-linker is equivalent to a physical cross-linking point in the particleboard, and is "anchored" with the bamboo and wood shavings by the adhesive, which will limit the further expansion of microcracks into large cracks, making the slab denser and having the effect of strengthening and toughening.
[0085] The above embodiments are used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention.
Claims
1. A method for preparing an environmentally friendly particleboard, characterized in that: The preparation method comprises the following steps: Step (1), preparing wood shavings: peeling, screening and removing impurities from bamboo and wood waste, adding the waste to a pulverizer, and processing the waste into wood shavings with a length of 100-120 mm, a width of 20-50 mm and a thickness of 0.3-0.5 mm to obtain wood shavings raw materials; Step (2), preparing rubber-mixed wood shavings: drying the wood shavings raw material, placing them in a drum rubber mixer, adding an environmentally friendly flame-retardant and mildew-proof adhesive and paraffin wax, stirring at 500-800 r / min for 1-3 hours, and drying to a moisture content of 3-5wt% to obtain rubber-mixed wood shavings; Step (3), preparing an environmentally friendly particleboard: manually laying the mixed glue wood chips into a single-layer slab, installing it in a steel film frame to form a three-layer structure of an upper and lower surface layer and a core layer, placing it in a hot press for hot pressing, demolding and curing, and obtaining an environmentally friendly particleboard.
2. The method for preparing the environmentally friendly particleboard according to claim 1, characterized in that: In the step (2), the mass ratio of the wood shavings raw material, the environmentally friendly flame retardant and mildew-proof adhesive, and the paraffin is 100:3-15:2-4.
3. The method for preparing the environmentally friendly particleboard according to claim 1, characterized in that: In the step (3), the hot pressing pressure is 3-6 MPa, the hot pressing time is 8-15 min, and the hot pressing temperature is 130-150°C.
4. The method for preparing the environmentally friendly particleboard according to claim 1, characterized in that: The method for preparing the environmentally friendly flame retardant and mildew-proof adhesive in step (2) comprises the following steps: Step S1, under a nitrogen atmosphere, add pentaerythritol glycidyl ether and ethanol into a reaction flask, stir evenly, add hexadecyl dimethyl tertiary amine and hydrochloric acid, stir to react, and after the reaction is completed, perform vacuum distillation, and recrystallize with a mixed solvent of acetone and ethyl acetate to obtain a long-chain quaternary ammonium salt intermediate; Step S2, under a nitrogen atmosphere, add a long-chain quaternary ammonium salt intermediate and acetonitrile to a reaction flask, stir evenly, add epichlorohydrin and sodium hydroxide, stir to react, and after the reaction is completed, perform reduced pressure distillation to obtain a polyepoxy quaternary ammonium salt cross-linking agent; Step S3, the soy protein, polyhydroxyphytic acid, and graphene oxide dispersion are mixed evenly, ultrasonically treated for 15-25 minutes, and then a polyepoxy quaternary ammonium salt crosslinker is added, placed in a high-speed shear dispersion homogenizer, and vigorously homogenized at room temperature for 20-40 minutes to obtain an environmentally friendly flame retardant and mildew-proof adhesive.
5. The method for preparing the environmentally friendly particleboard according to claim 4, characterized in that: In the step S1, the mass ratio of pentaerythritol glycidyl ether, hexadecyl dimethyl tertiary amine and hydrochloric acid is 100:305-330:15-25.
6. The method for preparing the environmentally friendly particleboard according to claim 4, characterized in that: In step S1, the reaction temperature is 65-80° C. and the reaction time is 24-48 hours.
7. The method for preparing the environmentally friendly particleboard according to claim 4, characterized in that: In the step S2, the mass ratio of the long-chain quaternary ammonium salt intermediate, epichlorohydrin and sodium hydroxide is 100:28-40:10-15.
8. The method for preparing the environmentally friendly particleboard according to claim 4, characterized in that: In step S2, the reaction temperature is 45-60° C. and the reaction time is 5-12 h.
9. The method for preparing the environmentally friendly particleboard according to claim 4, characterized in that: In the step S3, the mass ratio of soy protein, polyhydroxyphytic acid, graphene oxide dispersion and polyepoxy quaternary ammonium salt crosslinking agent is 100:4-8:20-35:2-10.
10. An environmentally friendly particle board, characterized in that: Obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of antibacterial, mildew-proof and environment-friendly particleboard
CN106863528B
Preparation method of multi-quaternary ammonium salt fungicide
CN105900979A
Bamboo-based plate and manufacturing method thereof
CN106239688A
Shaving board containing mildew preventing agent and manufacturing method of shaving board
CN108162124A
Preparation method of bacterium-inhibiting resin for yoga ball
CN108948634A
Cited By
High-strength graphene oxide bamboo oriented strand board and preparation method thereof
CN121515288A